Penguatan Wawasan Kebangsaan peserta didik di MTs. Raudlatul Hasaniyah melalui Pembelajaran Pendidikan Kewarganegaraan - Alifah Yulia Putri; Uswatun Hasanah; Ludfi Arya Wardana (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This research was conducted in order to find out how the development of the National Insight of students at MTS Raudlatul Hasaniyah through Citizenship Education Learning. The subjects in this study were students. The method used in this study is a qualitative approach using data collection techniques from observation, documentation and interviews. This research shows that apart from the students themselves, the teacher's role is also very important in strengthening nationalism. So as to create Citizenship Education learning activities to strengthen National Insight. In implementation, students must play an active role such as asking questions, concluding learning outcomes, and giving opinions. The teacher only helps if there are obstacles, except if students have delays in thinking / have special needs the teacher will motivate students to learn. Strengthening National Insight can also be seen from the development of attitudes and character of students during learning takes place. Like when paying attention to the material and the activeness of asking questions. Lack of literacy is an inhibiting factor at MTS Raudlatul Hasaniyah. The solution that can be done by the teacher is to guide students in learning and direct practice in implementing Strengthening National Insights.